PEMANFAATAN APLIKASI PENCARIAN LAYANAN RUMAH SAKIT DALAM MEMPERMUDAH AKSESIBILITAS MASYARAKAT - Zaky, Abdul; Bisra, Marido; Purnamasari, Devi (Awal Bros Journal of Community Development, 2023)
Pekanbaru City is the most populous city in Riau province which has 31 hospitals that provide various services. The distribution of hospitals affects the distribution of services, especially polyclinics. This can indirectly affect the degree of public health. This community service aims to introduce a prototype in the form of an Android-based application that helps people find hospitals in Pekanbaru City that provide the services needed. This Hospital Service Search Application in Pekanbaru City makes it easier and faster for people to find the health services they need. The Community Service carried out begins with the design of the Health Service Search Application in Pekanbaru City. The next activity is to conduct a function test and feasibility test on the Android application. The results of the function test and feasibility test are considered quite good with a value of 100% functioning and 87,5% said to be feasible. Workshop activities were carried out on several occasions, namely for high school students, the general public, students, and patients in hospitals. The results of this workshop activity generated very high interest from the community. Activity evaluation was carried out by distributing questionnaires where 83% of respondents considered this application to be very much needed by the community, while the rest stated that it was not needed. Based on the application concept, 70% of respondents stated that the application was good, 25% of respondents stated that this application needed to be improved and 5% of respondents stated that this application was not good. This Hospital Health Service Search Application is based on Android and this Application can be upgraded to be registered on services that can be accessed by the entire community for free.